Culture Semiology of AL-mahzomon Novel by Hany AL-raheb (Journal of Hama University, 2024)
This research deals with the rooting of the term Semiology of culture and the application of its tools to the novel AL-Mahzomon by the great writer Hany AL- Raheb because this novel deals with thought and culture related to an important time stage and the critical analysis included a study of the narrative text lessons through: Cultural boundaries that consist of: (Center, margin, culture, not culture), plot, and dialogue, and it was necessary to define the term semiotics and culture.
Keywords: Semiology; Semiotic; Culture; Semiotic of culture; semiology of culture; ALmahzomon; Hany Al raheb